Analysis and interpretation of regional gravity and magnetic data associated with the Mesoproterozoic Nipigon Embayment intrusive rocks, Canada (2024)
The Nipigon Embayment in Ontario, Canada, represents a unique geological setting characterized by mafic and ultramafic igneous rocks associated with a mid-continent rifting event approximately 1.1 billion years ago. This study used regional gravity and magnetic datasets to analyze the subsurface geometry and depth extent of these formations. By applying qualitative and quantitative geophysical methods, such as derivative filters and forward modelling, the research reveals boundaries of regional bodies, as well as constraints for magnetic and gravity anomalies in this region. The study proposes that the Nipigon Embayment could represent a third, incomplete arm of the Midcontinent Rift System, with its dimensions and configurations providing insights into early rift tectonics. This work highlights the Embayment's geological importance, emphasizing the need for further integrated geophysical modelling.